2008
DOI: 10.1145/1473195.1473227
|View full text |Cite
|
Sign up to set email alerts
|

Fostering individual learning

Abstract: In this paper we describe an instructional tactic that promotes individual learning. The tactic was developed to cope with the relatively high IS students' failing rate and to support the development of effective learning habits (to be used in collaboration contexts as well). The learning process is based on a unique individual assignments design for a Computer Organization and Programming course. The accompanying study revealed encouraging quantitative and qualitative results. Overall student's failing rate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This was done in order to minimize the possibility of sharing some or all of the assignment. This personal and unique assignments tactic [1] has been used in previous studies and was found to be effective especially for the current students' generation.…”
Section: The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…This was done in order to minimize the possibility of sharing some or all of the assignment. This personal and unique assignments tactic [1] has been used in previous studies and was found to be effective especially for the current students' generation.…”
Section: The Studymentioning
confidence: 99%
“…All assignments were uniquely individualized due to the lecturer previous good experience with this tactic. Personal and individual assignments [1] imply that each student receives a different assignment so sharing or "borrowing" the solution or parts of the solution is impossible. As was demonstrated already this tactic has a positive influence on the students' learning habits [1], [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the author's experience with individual and unique assignments [42], [43] it was decided to implement this tactic as well. This was done mainly, in an effort to further reduce the failing students' percentage.…”
Section: The Studymentioning
confidence: 99%